Identification of the benefits, enablers and barriers to integrating junior pharmacists into the ward team within one UK-based hospital - Hung MY; Wright DJ; Blacklock J; Needle RJ (Dove Medical Press, 2017)
Man Yui Hung,1 David John Wright,2 Jeanette Blacklock,2 Richard John Needle1,2 1Pharmacy Department, Colchester Hospital University NHS Foundation Trust, Colchester, 2School of Pharmacy, University of East Anglia, Norwich, UK Introduction: A high nurse-vacancy rate combined with high numbers of applications for junior pharmacist roles resulted in Colchester Hospital University National Health System Foundation Trust trial employing junior pharmacists into traditional nursing posts with the aim of integrating pharmacists into the ward team and enhancing local medicines optimization. The aim of the evaluation was to describe the implementation process and practice of the integrated care pharmacists (ICPs) in order to inform future innovations of a similar nature.Methods: Four band 6 ward-based ICPs were employed on two wards funded within current ward staffing expenditure. With ethical committee approval, interviews were undertaken with the ICPs and focus groups with ward nurses, senior ward nurses and members of the medical team. Data were analyzed thematically to identify service benefits, barriers and enablers. Routine ward performance data were obtained from the two ICP wards and two wards selected as comparators. Appropriate statistical tests were performed to identify differences in performance.Results: Four ICPs were interviewed, and focus groups were undertaken with three junior nurses, four senior nurses and three medical practitioners. Service enablers were continuous ward time, undertaking drug administration, positive feedback and use of effective communication methods. Barriers were planning, funding model, career development, and interprofessional working and social isolation. ICPs were believed to save nurse time and improve medicines safety. The proportion of patients receiving medicine reconciliation within 24 hours increased significantly in the ICP wards. All ICPs had resigned from their role within 12 months.Discussion: It was believed that by locating pharmacists on the ward full time and allowing them to undertake medicines administration and medicines reconciliation, the nursing time would be saved and medicines safety improved. There was however significant learning to be derived from the implementation process, which may enable similar future models to be introduced more successfully. Keywords: integration, pharmacist, ward team, medicines administration, medicines reconciliation, lose integration